Inserção profissional docente no Estado de São Paulo: a escola de formação e o curso para professores ingressantes da SEE/SP - Mirisola, Cristiane Dias (2012)
Inserted in the big topic on the teachers training and the teachers professional development, the qualitative research analyzes the official justification expressed in the documents and in the legislation which create and establish the EFAP the School of Teachers Training and Improvement of the State of Sao Paulo "Paulo Renato Souza Costa". The qualitative research also describes and analyzes the Specific Training Course for teachers approved by the examination of the State Educational Secretary of São Paulo, under the responsibility of the EFAP. This study aims to identify and discuss the conception of teacher training and the expected profile of teachers to the educational project of the state of São Paulo. This project responds, on one hand, to a demand attested by the literature, and on the other hand to a need of control, by the State, over the teachers identity and performance due to the quality of the education. Another goal of this study is to identify how that control, which aims to unconditional participation and standardization, is built. As theoretical referential, the research used: authors who study the teacher training such as Barroso, Candau, Pereira, Marin among others; authors who are committed to the study of professional development and the teachers integration such as Marcelo, Huberman and Veenman; and authors who work with the managers discourse and mechanisms of control institutionalized by the managers in order to format the teacher s work, such as Viñao Frago and Lawn. The results obtained through the document analysis of the legislation, speeches and interviews enable to claim that the Course of Entering Teachers is a action of professional beginning with unique features. Due to the fact that this course is a result of an educational policy focused on the control of the teacher s performance and on the improvement of the quality of education, it accepts the teaching function as a technical work carried out efficiently and a time saving way in order to achieve goals that can be shown in figures. The results prove the ambiguity of the Course of Entering Teachers: not only does it promote the professional beginning and the teachers welcoming highlighting aspects that locate the teacher profession, but also it tends to standardize the teachers performance